The nature of corporate crime in law enforcement of the criminal justice system in Indonesia - Hadi Supriyanto (Jurnal Hukum Volkgeist, 2020)
Law in its nature is not only used to control conduct that already occurs in society and sustain established behaviors patterns, but the law often contributes to its use as a means. The study revealed 1). Corporate Criminal Liability was an attempt to put the company in the sense of Equality Under the law with a view to achieving legal certainty, fairness and usefulness, 2) Control of corporate criminal penalties was implemented in several laws through a common formulation of the key criminal fines, 3) law enforcement against corporate crime can be achieved through a) Normative Approach. Therefore, it is required that the state will specifically articulate the responsibility for corporate criminal liability through legislative and executive agencies and what kind of liability can be formally demanded of the corporation as the object of criminal liability (legal policy), since the assessment of corporate errors is the basis of material for the demand of corporate criminals.